The Effect of Vitamin D3 Supplementation on Interleukin-6 and PRESS Score in Children with Pneumonia and Vitamin D Deficiency - Setyoningrum, Retno Asih; Kristianto, Wigit; Chafid, Arda Pratama Putra; Hapsari, Rika; Syafa'ah, Irmi (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Pneumonia is a significant health issue in children under 5 years old. Vitamin D may help to reduce childhood mortality, morbidity, and interleukin-6 (IL-6) levels in children with pneumonia, but the evidence is still limited and controversial. This study aimed to evaluate the effect of vitamin D3 supplementation on IL-6 levels and clinical manifestations in children with pneumonia and vitamin D inadequacy. Methods: This was a randomized, placebo-controlled, and double-blinded trial study. Twenty-eight children diagnosed with pneumonia and vitamin D deficiency were enrolled and divided into a supplementation (n=15) or placebo group (n=13). Children were given a single dose (100,000 international units/IU) of vitamin D3 or placebo on the first day of hospitalization. Clinical manifestations were assessed by the Pediatric Respiratory Severity Score (PRESS). Results: The level of 25-hydroxyvitamin D (25-OH D3), IL-6, and PRESS score at baseline showed no significant difference between groups. Seven days post-supplementation, only the PRESS score showed a significant difference between groups (p=0.025). Analysis of the vitamin D3 group showed a significantly increased 25-OH D3 level and a reduced PRESS score (p=0.039 and p=0.02, respectively). Conclusion: A single high dose of vitamin D3 supplementation in children with pneumonia and inadequate vitamin D levels helps elevate 25-OH D3 levels and reduce clinical manifestations, as indicated by the PRESS score.